Pengaruh Rasio Solid Liquid Dan Penambahan Graphene Nanosheets Terhadap Kuat Tekan Mortar Geopolimer Berbasis Palm Oil Fuel Ash (POFA) Dan-Flyash Batu Bara - Muhammad Zaqi; Amun Amri; Desi Heltina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Geopolymer mortar is a material that has high SiO2 and Al2O3 content and has the potential to be used as a base for making geopolymer mortar. This study aims to make geopolymerbased mortar (POFA) and coal flyash with the addition of graphene, and variations in the addition of graphene to the mechanical and morphological properties of the geopolymer mortar. The preparation of the geopolymer mortar includes several steps, namely the preparation and mixing of materials with various solid liquid ratios of 72:28, 60:40, and 80:20, then proceed with the preparation of an activator alkaline solution (10 M NaOH + Sodium silicate) and the addition of graphene with variations of 0%, 1% wt, 2% wt, and 3% wt. The results of the morphological analysis showed that the increased cavity that was formed increased along with the increase in the amount of graphene added. While the results of the compressive strength test showed that the highest compressive strength was obtained at 19,2 Mpa at a solid liquid ratio of 60:40 and the lowest compressive strength was obtained at 12,8 Mpa at a solid liquid ratio of 80:20. Keywords : geopolymer mortar, coal fly ash, graphene, POFA